2012
DOI: 10.1136/vr.100401
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase protein levels in dogs with mast cell tumours and sarcomas

Abstract: The acute phase proteins (APP) form part of a non-specific host response to inflammation. They may be induced by a range of different causes, including infection, inflammation, cancer and trauma. As they form part of the earliest response to such insults, they have potential for early identification of disease. In people, APP levels have been shown to correlate both with the extent of disease and also the prognosis in several forms of neoplasia, including prostate, oesophageal and colorectal cancer. As such, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
2
13
3
Order By: Relevance
“…), mast cell tumours and sarcomas (Chase et al . ) and mammary tumours (Planellas et al . ) compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), mast cell tumours and sarcomas (Chase et al . ) and mammary tumours (Planellas et al . ) compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…2007 ), histiocytic sarcoma (Nikolic Nielsen et al . 2013 ), mast cell tumours and sarcomas (Chase et al . 2012 ) and mammary tumours (Planellas et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among those cancer biomarkers, thymidine kinase 1 (TK1), C‐reactive protein (CRP), α1‐acid glycoprotein (AGP) and haptoglobin have been most extensively evaluated for their correlation with cancer. Measurement of serum TK1 level has been proven to be a useful diagnostic tool for detection of various types of malignant tumours in dogs as well as prediction of clinical outcomes of anti‐cancer therapy in lymphoma patients . However, additional measurement of CRP, a widely accepted biomarker of inflammation, in serum is necessary to improve the limitation of TK1 activity assessment for detecting solid tumours other than hemangiosarcoma in dogs .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TNFAIP8 expression is significantly associated with a higher risk of prostate cancer recurrence (27). A previous study demonstrated that APP expression levels correlated with the extent of disease and the prognosis in several forms of cancer (28). In addition, SYNE1 is a promising biomarker in colitis-associated colorectal cancer (29).…”
Section: Discussionmentioning
confidence: 99%